Heterogeneous Fenton Degradation of Patulin in Apple Juice Using Carbon-Encapsulated Nano Zero-Valent Iron (CE-nZVI) - Notemba Silwana; Blanca Calderón; Seteno Karabo Obed Ntwampe; Andrés Fullana (Foods, 2020)
Patulin (PAT), a mycotoxin found mainly in matured apples, is produced by different species of fungi, mainly Penicillium expansum, and is found in various fruits and vegetables used to produce juice. Little focus has been placed on nano-technological methods for the mitigation of this problem. In this work, carbon-encapsulated nano-zero valent iron (CE-nZVI) particles were synthesized and used as heterogeneous Fenton agents for the degradation of PAT in apple juice. The particles were found to have a spherical shape with a diameter of 130 ± 50 nm. In a heterogeneous Fenton degradation (involving CE-nZVI) process, a concentration of 0.05 g/L CE-nZVI with 0.5 mM H2O2 was used. Since the Fenton oxidation process is pH-dependent, placebo degradation was observed at varying pH conditions with an average percentage of PAT degradation of 27.8%, 87.0%, 98.0%, and 99.75% at pH 6, 5, 4.5, and 3.5 respectively, between 1 min to 4 h in a water matrix. In a juice matrix, at the regular pH of juice (3.6), percentage PAT degradation of 72% and 89% was obtained after a 2-h treatment using heterogeneous Fenton oxidation (CE-nZVI/H2O2) systems, using 0.5 mM H2O2 and 1 mM H2O2, respectively.